Analisis Intensitas Konsumsi Energi RS Medirossa Cikarang - Sielvya Rahma Maulida; Mia Galina; Joni Welman Simatupang (Journal of Electrical And Electronics Engineering, 2019)
Medirossa Hospital is one of the health care centers in the city of Cikarang which in its operations does not only focus on the customer excellent services but also pay attention to the comfort of the environment and the completeness of the health facilities. One factor that determines the convenience of a hospital is the intensity of lighting. From the observations made by the authors of several rooms at Medirossa Cikarang Hospital, namely the casemix room, medical records, VIP treatment, and the hall leading to the second floor has less bright lighting. This observation was carried out by surveying 26 respondents who were hospital employees and visitors. From the observation, 53% of respondents stated that the room was "not bright enough." To find out whether the lighting in the room surveyed is actually less than the Indonesian National Standard (SNI 6197: 2011), it is necessary to measure the intensity of lighting using a measuring instrument, calculating and analyzing of IKE (intensity of energy consumption) values, which can then be continued with lighting improvement if the IKE value is below the applicable lighting standard. Based on the results of calculations and analysis it was found that the value of IKE RS Medirossa Cikarang is 248.603 kWh/m² year. This value indicates that electricity consumption is efficient, but has not fulfilled the applicable standards. To achieve the intensity of lighting in the rooms that have been surveyed, it is necessary to add a lamp that resulted in additional load of 748 Watt. This study aims to provide analysis and suggestion to regarding the intensity of energy consumption of RS Medirossa Cikarang for hospital lighting improvements which in turn can improve the comfort of hospital employees and visitors